IMPACT OF MEDICAL REPRESENTATIVES ON ACCEPTANCE OF HIGH PRICED PRESCRIPTION DRUGS BY DOCTORS: A STUDY - Silveira, Cedric Thomas (International Journal of Research -GRANTHAALAYAH, 2021)
Do rapport and information have any bearing on doctors’ preference for high priced products? This was the study undertaken by me. Doctors in urban areas usually do not have the time to develop rapport with the medical representatives and as a result should not accept high priced products. On the other hand information too will not influence prescription of high priced products because they depend upon peer advice, seminars and conferences and evaluation tests. The situation among rural doctors is different wherein they should welcome medical representatives and their information and develop a rapport with them and thereby prescribe high priced products. However it was seen that developing a rapport was not enough for rural doctors to prescribe high priced products as they looked into the affordability of their patients first. However information was accepted and even high priced products were prescribed by doctors. On the other hand urban doctors were not influenced by either rapport or information and depended on conferences, seminars, peer advice and evaluation tests before prescribing high priced products. The study was conducted on 200 urban doctors and 200 rural doctors in Goa. A personal interview was conducted wherein the questionnaire was direct and structured. Pearson’s coefficient of correlation was used to determine if information and rapport had any correlation with doctors prescribing high priced products.